Pengaruh Persepsi Masyarakat Tentang Wakaf Uang Terhadap Minat Berwakaf Uang di Kota Surabaya - Ismawati, Yuliana; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2019)
The purpose of this study was to determine the effect of public perceptions of cash waqf on interest in representing money in the city of Surabaya. The independent variable in this study consisted of one variable, namely the perception variable about money waqf was measured using indicators of experience, knowledge, understanding and evaluation or assessment. The dependent variable in this study is interest and is measured using indicators of Inner Self, social motives and emotional or feeling factors. This research was conducted with an associative quantitative approach. The sample in this study amounted to 100 respondents using accidental sampling technique. This study uses a questionnaire with a likert scale. The results of this study indicate that the public perception variable about mony waqf has a significant effect on interest variables representing money in the city of Surabaya. As for based on the test results of the coefficient of determination (R2) shows that the perception variable has an influence of 36,9% on interest variables representing money.